An observational prospective cohort study of the epidemiology of hospitalized patients with acute febrile illness in Indonesia - Gasem, Muhammad Hussein; Kosasih, Herman; Tjitra, Emiliana; Alisjahbana, Bachti; Karyana, Muhammad; Lokida, Dewi; Neal, Aaron; Liang, C. Jason; Aman, Abu Tholib; Arif, Mansyur; Sudarmono, Pratiwi; Suharto; et al. (PLOS Neglected Tropical Diseases, 2020)
Background The epidemiology of acute febrile illness, a common cause of hospitalization in Indonesia, has not been systematically studied. Methodology/Principal findings This prospective observational study enrolled febrile patients (temperature ≥38°C) aged ≥1 year from July 2013 until June 2016 at eight government referral teaching hospitals in seven provincial capitals in Indonesia. Patients were managed according to the hospital standard-of-care (SOC), and blood samples were drawn for molecular and serological assays. Clinical data, laboratory results, and specimens for additional tests were collected at enrollment, days 14–28, and at three months. Regular follow-up visits were then scheduled for every three months either until symptoms resolved or until one year. In total, this study included 1,486 adult and pediatric patients presenting with multi-organ (768, 51.7%), gastrointestinal (497, 33.0%), respiratory (114, 7.7%), constitutional (62, 4.2%), skin and soft-tissue (24, 1.6%), central nervous system (17, 1.1%), or genitourinary (4, 0.3%) manifestations. Microbiological diagnoses were found in 1,003/1,486 (67.5%) participants, of which 351/1,003 (35.0%) were not diagnosed during hospitalization using SOC diagnostic tests. Missed diagnoses included all cases caused by Rickettsia spp., chikungunya, influenza, and Seoul virus. The most common etiologic agents identified were dengue virus (467, 46.6%), Salmonella spp. (103, 10.3%), and Rickettsia spp. (103, 10.3%). The overall mortality was 89 (5.9%). Conclusions/Significance Febrile illness in Indonesia has various microbiologic etiologies and substantial overall mortality. Diagnostic limitations and lack of epidemiologic data resulted in potentially treatable, and at times fatal, diseases being missed.